2020
DOI: 10.3233/bmr-181241
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of conservative treatment with and without neural mobilization for patients with low back pain: A prospective, randomized clinical trial

Abstract: BACKGROUND: Low back pain (LBP) is a common problem that causes pain, disability, and gait and balance problems. Neurodynamic techniques are used in the treatment of LBP. OBJECTIVE: The aim of this study was to compare the effects of electrotherapy and neural mobilization on pain, functionality, gait, and balance in patients with LBP. MATERIALS AND METHODS: A total of 41 patients were randomly assigned to either the neural mobilization group (NMG, n= 20) or electrotherapy group (ETG, n= 21). Assessment tools u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 29 publications
1
24
0
Order By: Relevance
“…Although NM has shown some positive effects in treating people with musculoskeletal pain [ 6 9 ], previous systematic reviews have shown limited or inconclusive evidence to support the use of this intervention in these population. As stated before, most previous reviews have focused only on specific musculoskeletal conditions or only on limited outcomes of interest, with a narrow approach of the NM application [ 17 , 46 51 ], with the exception of three of them [ 14 , 16 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although NM has shown some positive effects in treating people with musculoskeletal pain [ 6 9 ], previous systematic reviews have shown limited or inconclusive evidence to support the use of this intervention in these population. As stated before, most previous reviews have focused only on specific musculoskeletal conditions or only on limited outcomes of interest, with a narrow approach of the NM application [ 17 , 46 51 ], with the exception of three of them [ 14 , 16 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…A therapeutic intervention that has been applied to treat patients with musculoskeletal conditions is neural mobilization (NM), which has shown positive effects in reducing pain and improving functioning [ 6 9 ]. NM consists of combinations of joint movements that promote the gliding or the tensioning of the neural tissue and that can be performed both passively by the health professional or actively by the individual [ 10 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…In clinical practice, it is frequent to use a combination of several manual techniques, and the inclusion of the NM to other OMPT or SST techniques has also been studied among the craniofacial region [ 65 ]. It has been shown that the addition of NM to the OMT techniques may obtain greater therapeutic effects of pain reduction among cervical radiculopathy patients [ 27 , 66 , 67 ]. It is theorised that NM may restore nerve homeostasis by mobilisation (passive or active) of the nerves and surrounding structures of the nervous system [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…The results of this study are in line with previous studies which reported that neural mobilization techniques improved pain and function in patients with nerve related low back pain. 1,1517 Additionally, neural mobilization has been reported as a superior post-surgical intervention compared with myofascial release and lumbar stabilization exercises alone in improving pain and functional disability after lumbar spinal fusion. 18…”
Section: Discussionmentioning
confidence: 99%